2020
DOI: 10.1177/0003489420930773
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acamprosate on Chronic Tinnitus: A Randomized-Controlled Trial

Abstract: Objectives: Tinnitus is a common and distressing otologic symptom, with various probable pathophysiologic mechanisms, such as an imbalance between excitatory and inhibitory mechanisms. Acamprosate, generally used to treat alcoholism, is a glutaminergic antagonist and GABA agonist suggested for treating tinnitus. Thus, we aimed to evaluate the efficacy and safety of acamprosate in the treatment of tinnitus. Methods: The current randomized-controlled trial study included 20 subjects with chronic tinnitus. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…After treatment, the reduction of latency of CAP was statistically significant, which indicates a robust and synchronized firing of the neuron fibers, along with the improvement of the self-report tinnitus questionnaire scores among tinnitus patients. However, SP/AP ratios did not change significantly in one study [ 179 ]. CAP amplitudes were suppressed and thresholds increased in tinnitus patients induced by sodium salicylate in one study [ 180 ].…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After treatment, the reduction of latency of CAP was statistically significant, which indicates a robust and synchronized firing of the neuron fibers, along with the improvement of the self-report tinnitus questionnaire scores among tinnitus patients. However, SP/AP ratios did not change significantly in one study [ 179 ]. CAP amplitudes were suppressed and thresholds increased in tinnitus patients induced by sodium salicylate in one study [ 180 ].…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
“…Moreover, some indirect evidence, such as EcochG can be used to detect synaptopathy, and synaptopathy can cause tinnitus [ 32 , 177 ]. After some time of treatment, tinnitus is relieved and the electrocochleogram is also changed [ 179 , 181 , 182 ]. These pieces of evidence show that electrocochleogram has the potential to detect tinnitus, but more in-depth research needs to be carried out in the future.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (13 of 23) reported THI metrics both before and after treatment (14,15,(20)(21)(22)(23)(24)(25)(27)(28)(29)31,33). Three studies reported TSI metrics (16,18,33), 2 studies reported TFI metrics (26,29), 2 studies reported THQ metrics (17,30), 11 studies reported VAS-L measurements (12,13,18,19,21,22,25,28,(32)(33)(34), 2 studies reported VAS-Aw measurements (25,28), 5 studies reported VAS-An measurements (25,28,29,31,34), 3 studies reported frequency matching measurements (25,29,33), 7 studies reported loudness matching measurements (17,19,21,25,26,29,33), 4 studies reported the MML (19,21,…”
Section: Analysis Of Statistical Measuresmentioning
confidence: 99%
“…Furthermore, in tinnitus patients without specific or treatable origin, there were abnormal hyperactivity in brain multiple regions [11] . Therefore, new pharmacologic strategy for managing brain abnormal hyperactivities had been proposed [12] . However, there is a lack of clarity regarding the evidence about the efficacy for most of these alternative treatments.…”
Section: Introductionmentioning
confidence: 99%